An omni-directional optical antenna and its beam control method based on the EC-KPA algorithm for mobile FSO - Shang, Tao; Yang, Yintang; Li, Weixu; Wang, Xin; Jia, Jijun (Optics express, 2013)
In order to ensure the communication link stability in mobile FSO system, a new omni-directional optical antenna is designed. Being aimed at discontinuous tracking, a novel beam control method based on the error correction Kalman prediction algorithm (EC-KPA) is proposed. The comparison of EC-KPA and the conventional Kalman prediction algorithm (KPA) is given. Numerical simulations about beam control method are carried out. The results show that the prediction accuracy of EC-KPA is improved about 77% than that of KPA in Gaussian noise situation, and that the increase is up to 12.92 times in strong noise situation. Therefore, the beam control method is feasible, and this optical antenna can meet the demands of fast mobile FSO.